(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
The original published version of the article contained two errors: (1) In Table 1B: tomato was not indicated as host plant for T. evansi (2) In Figure 1: After carefully looking at the previously drawings of T. ludeni body parts, we concluded that it is necessary to give new, more precise drawings of male aedeagus and female tibia/tarsus I